Discovery of an acidic, thermostable and highly NADP+ dependent formate dehydrogenase from Lactobacillus buchneri NRRL B-30929 - Alpdagtas, Saadet; Yucel, Sevil; Kapkac, Handan Acelya; Liu, Siqing; Binay, Baris (SPRINGER, 2018)
To identify a robust NADP(+) dependent formate dehydrogenase from Lactobacillus buchneri NRRL B-30929 (LbFDH) with unique biochemical properties. A new NADP(+) dependent formate dehydrogenase gene (fdh) was cloned from genomic DNA of L. buchneri NRRL B-30929. The recombinant construct was expressed in Escherichia coli BL21(DE3) with 6 x histidine at the C-terminus and the purified protein obtained as a single band of approx. 44 kDa on SDS-PAGE and 90 kDa on native-PAGE. The LbFDH was highly active at acidic conditions (pH 4.8-6.2). Its optimum temperature was 60 A degrees C and 50 A degrees C with NADP(+) and NAD(+), respectively and its T-m value was 78 A degrees C. Its activity did not decrease after incubation in a solution containing 20% of DMSO and acetonitrile for 6 h. The K-M constants were 49.8, 0.12 and 1.68 mM for formate (with NADP(+)), NADP(+) and NAD(+), respectively. An NADP(+) dependent FDH from L. buchneri NRRL B-30929 was cloned, expressed and identified with its unusual characteristics. The LbFDH can be a promising candidate for NADPH regeneration through biocatalysis requiring acidic conditions and high temperatures.
Keywords: Acidic formate dehydrogenase; Biochemical and kinetic characterization; Highly NADP(+) dependent formate dehydrogenase; Lactobacillus buchneri NRRL B-30929; Solvent stable; Thermostability; HIGH-RESOLUTION STRUCTURES; COENZYME SPECIFICITY; COFACTOR SPECIFICITY; ENZYME; Biotechnology & Applied Microbiology